Rozwój lokalny w województwie lubelskim jako efekt uwarunkowań geograficznych - Gorzym-Wilkowski, Waldemar A. (Local Development in Lublin Voivodship as an Effect of Geographical Determinants, 2007)
Local socio-economic development depends to a great extent on activities of gmina's government. However, geographical factors have significant impact on it. The findings of conducted analysis say that the main factors are those which stimulate the development of non-agricultural activities, sphere of service, in particular. Those factors include: situation within agglomerations and in the neighborhood of important transit communication routes. Situation within attractive areas for tourism and recreation is an important stimulator of the development among natural characteristics of space. Whereas the influence of soil quality on the local development hasn't been observed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 370-378